Phraseological representation of the concept «sin» in Belarusian and Ukrainian (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article determines the place and the role of phraseological units of the Belarusian and the Ukrainian languages in representation of the concept «sin» and singles out common and specific features of the ethno-cultural consciousness through comparison of the number of phraseological units and their imagery being the basis for the religion to enter the language and culture of each people.
Keywords: phraseological unit; concept; sin; language; culture; religion; the Belarusians; the Ukrainians